STORY GRAMMAR STRATEGY AS A MEANS TO IMPROVE STUDENTS READING COMPREHENSION ACHIEVEMENT OF NARRATIVE TEXT AT THE NINTH GRADE OF SMPN 1 SELAT IN ACADEMIC YEAR 2020/2021 - Kadek Wahyu Septian Bagaskara; Ni Luh Putu Dian Sawitri; Ida Bagus Nyoman Mantra (Academic Journal on English Studies (AJOES), 2021)
Reading is crucial to be mastered by the students. However, reading has become the majorproblem faced by most of the students especially the ninth-grade students of SMPN 1 Selat inthe academic year 2020/2021. The present study was intended to answer the research problemas follow: Can story grammar strategy improve students reading comprehension achievement?This research was designed as a classroom action research. The subjects were IX A class ofSMP N 1 Selat which consisted of 29 students. Based on the result of preliminary observationand pre-test, it showed that the students still have low reading comprehension skill. In anattempt to solve this, story grammar strategy was implemented in two cycles. The result ofposttest at the end of each cycle clearly proved significant improvement of students’ readingcomprehension. Furthermore, this research also indicated positive responses from the subjectsregarding the implementation of story grammar strategy in improving subjects’ readingcomprehension skill. In conclusion, the present classroom action research proved that readingskill of the ninth-grade students of SMPN 1 Selat in the academic year 2020/2021 can beimproved through story grammar strategy.